Espaço, sociabilidade e segurança : perspectivas de encontro a partir de um estudo de caso no bairro Floresta - Schmitt, Paula Helena (2015)
Cities are moving scenarios in which complex social phenomena unwind. The combination formed by the loss of credibility of the public authorities in the management of collective life and the diffused social representations regarding the fear of violence can lead to a generalized feeling of insecurity, resulting in political alienation, spatial segregation, and the utilization of private resources for self-protection and self-restraint. What can be seen, therefore, is the lack of structure of the urban society by the reduction of spontaneous traffic in urban spaces and the possibilities of the encounter with the difference that, ultimately, enhances the risk scales. Therefore, through a case study in the Floresta neighborhood, in Porto Alegre/RS, in which proposes the tension of the relation between space, sociability, and safety, questioning the local social dynamics in its potential capability of producing cracks in the homogeneous and hegemonic tissue of the individual isolation, formulating an emancipatory rapture with the urban experience grounded in fear and a redefinition of social-spatial experience. Focus area: Penal System and Violence Research line: Violence, Crime, and Public Safety